Bilateral giant retinal pigment epithelial tears in hypertensive choroidopathy - Matsubara, Natsuki (Am J Ophthalmol Case Rep, 2019)
PURPOSE: To report a case of hypertensive choroidopathy with bilateral bullous serous retinal detachments (SRDs), retinal pigment epithelial detachments (PEDs), and giant retinal pigment epithelial (RPE) tears. OBSERVATIONS: A 68-year-old man with a history of hypertension and diabetes mellitus presented with bilateral visual loss of about 10 day's duration. He discontinued his oral medications for 2 months without the advice of a physician. At his first visit, the best-corrected visual acuities (BCVAs) were 0.02 in the right eye and 0.3 in the left eye (decimal notation), and the respective intraocular pressures were 15 and 13 mmHg. Bullous SRDs, large PEDs, and giant RPE tears were present bilaterally. Blot retinal hemorrhages and hard exudates were seen in the left eye. The systemic blood pressure was 231/77 mmHg, and bilateral lower leg edema was observed. Biochemical blood tests showed deteriorated renal function, hypoalbuminemia, and hyperglycemia. Ultra-wide-field fundus fluorescein angiography showed leakage at the areas of the SRDs and hyperfluorescent areas corresponding to the RPE tears bilaterally. Indocyanine green angiography showed hypofluorescent areas corresponding to the PEDs. Systemic computed tomography and magnetic resonance imaging were performed, and no malignancy was found. Based on these findings, hypertensive choroidopathy was diagnosed. A week after antihypertensive treatment, the SRDs and PEDs resolved bilaterally, and the BCVAs improved to 0.4 and 0.5 in the right and left eyes, respectively. The RPE tears remained in both eyes, although the SRDs and PEDs did not recur. CONCLUSIONS AND IMPORTANCE: Hypertensive choroidopathy must be considered in the differential diagnosis of SRDs and/or PEDs.